Cebranopadol, a Mixed Opioid Agonist, Reduces Cocaine Self-administration through Nociceptin Opioid and Mu Opioid Receptors - Shen, Qianwei; Deng, Yulin; Ciccocioppo, Roberto; Cannella, Nazzareno (Frontiers in Psychiatry, 2017)
Cocaine addiction is a widespread psychiatric condition still waiting for approved efficacious medications. Previous studies suggested that simultaneous activation of NOP and MOP receptors could be a successful strategy to treat cocaine addiction, but the paucity of molecules co-activating both receptors with comparable potency has hampered this line of research. Cebranopadol is a nonselective opioid agonist that at nanomolar concentration activates both NOP and MOP receptors and that recently reached phase III clinical trials for cancer pain treatment. Here, we tested the effect of cebranopadol on cocaine self-administration in the rat. We found that under a fixed-ratio-5 schedule of reinforcement cebranopadol (25 and 50 μg/kg) decreased cocaine but not saccharin self-administration, indicating a specific inhibition of psychostimulant consumption. In addition, cebranopadol (50 μg/kg) decreased the motivation for cocaine as detected by reduction of the break point measured in a progressive-ratio paradigm. Next, we found that cebranopadol retains its effect on cocaine consumption throughout a seven-day chronic treatment, suggesting a lack of tolerance development towards its effect. Finally, we found that only simultaneous blockade of NOP and MOP receptors by concomitant administration of the NOP antagonist SB-612111 (30 mg/kg) and naltrexone (2.5 mg/kg) reversed cebranopadol-induced decrease of cocaine self-administration, demonstrating that cebranopadol activates both NOP and classical opioid receptors to exert its effect. Our data, together with the fairly advanced clinical development of cebranopadol and its good tolerability profile in humans, indicate that cebranopadol is an appealing candidate for cocaine addiction treatment.